Lost Wages: The COVID-19 Cost of School Closures - George Psacharopoulos; Victoria Collis; Harry Anthony Patrinos; Emiliana Vegas (Global Labor Organization (GLO), 2020)
Social distancing requirements associated with COVID-19 (coronavirus) have led to school closures. In mid-April, the United Nations Educational, Scientific and Cultural Organization reported that 192 countries had closed all schools and universities, affecting more than 90 percent of the world's learners: 1.5 billion children and young people. The closures are expected to reduce learning and will lead to future losses in earnings and labor productivity. Schooling attainment leads to increased earnings. What is not known is how much earnings will decline due to the school closures. Starting with the fact that every year of schooling equates to 8-9 percent in additional future earnings, this paper uses the number of months of education closures to estimate the loss in marginal future earnings. The findings show that the school closures reduce future earnings, and this loss is equivalent to 15 percent of future gross domestic product. The school closures will have a large and long-lasting impact on the earnings of future workers. It is also likely that students from low-income countries will be affected most. These estimates are conservative, assuming that the closures will end after four months and school quality will not suffer.
Keywords: I26; I20; J24; 330; education; earnings; Covid-19